Respiratory symptoms in people living with HIV and the effect of antiretroviral therapy: a systematic review and meta-analysis. Issue 4 (24th October 2016) - Brown, James; Roy, Anjana; Harris, Ross; Filson, Sarah; Johnson, Margaret; Abubakar, Ibrahim; Lipman, Marc
Abstract : Background: Antiretroviral therapy (ART) has significantly altered the pattern of acute and chronic HIV-related disease. However, it is not clear what this means in terms of respiratory symptoms. We sought to investigate the association between HIV status and respiratory symptoms and how these have changed with the availability of ART. Methods: We searched Cochrane, Medline and Embase databases for studies published between 1946 and August 2015 comparing the prevalence of respiratory symptoms in populations with and without HIV infection. We undertook random effects meta-analysis of the main symptoms reported. We studied heterogeneity and completed sensitivity analyses and funnel plots. Results: From 5788 unique references identified, 24 papers provided relevant data: 18 documented the prevalence of cough and 11 examined the prevalence of breathlessness among other symptoms reported. Compared with the HIV negative, people living with HIV (PLWH) were more likely to have respiratory symptoms with pooled ORs for the prevalence of cough of 3.05 (95% CI 2.24 to 4.16) in resource-limited populations without access to ART; 2.18 (1.56 to 3.18) in resource-rich populations without access to ART and 1.11 (0.99 to 1.24) in resource-rich populations with access to ART. In resource-rich settings, although the availability of ART was associated with a reduction in the difference between HIV-positive and HIV-negative individuals, PLWH were more likely to report breathlessness, OR 1.39 (95% CI 1.11 to 1.73). Conclusions: Respiratory symptoms are more common in PLWH than controls. This association persists although at a reduced level in populations with access to ART.